2004
DOI: 10.1890/03-3107
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Induced Ocean Warming Causes Comprehensive Changes in Marine Benthic Communities

Abstract: One of the most commonly predicted effects of global ocean warming on marine communities is a poleward shift in the distributional boundaries of species with an associated replacement of cold‐water species by warm‐water species. However, these types of predictions are imprecise and based largely on broad correlations in uncontrolled studies that examine changes in the distribution or abundances of species in relation to seawater temperature. Our study used an 18‐year sampling program in intertidal and subtidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
174
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(181 citation statements)
references
References 25 publications
2
174
1
4
Order By: Relevance
“…This most likely indicates a decrease in suitable habitat (kelp) during that period, as already proposed by the descriptions of the professional divers. Climate change is affecting marine communities in numerous ways; however it has been argued that its indirect effect by the loss of habitat forming organisms is of even greater concern (Schiel et al, 2004). In this study we also showed an increase in decapod landing from 2010.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…This most likely indicates a decrease in suitable habitat (kelp) during that period, as already proposed by the descriptions of the professional divers. Climate change is affecting marine communities in numerous ways; however it has been argued that its indirect effect by the loss of habitat forming organisms is of even greater concern (Schiel et al, 2004). In this study we also showed an increase in decapod landing from 2010.…”
supporting
confidence: 57%
“…Kelp acts as both substratum for many sessile animals and algae and as habitat for mobile organisms living in and feeding directly on the kelp or their associated species (Duggins, 1980;Christie et al, 2009). A decline in habitat-forming subtidal kelp unsurprisingly results in major changes in near shore community composition (Schiel et al, 2004;Wernberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The intertidal algae and invertebrate datasets were collected at 3 sites along the central California coast (Schiel et al 2004). Each site has two 30 m transects at different tidal elevations (+0.3 m and +0.9 m mean lower low water).…”
Section: Dataset Descriptionsmentioning
confidence: 99%
“…En el caso de termoeléctricas costeras, el agua es obtenida del mar, lo que implica que grandes cantidades de organismos planctónicos son sometidos a rápidos incrementos de temperatura y presión, daños mecánicos por abrasión y efecto de biocidas antiincrustantes, provocando impactos negativos sobre su abundancia, composición y sobrevivencia (Bamber & Seaby 2004, Taylor 2006. Posteriormente, el agua utilizada es descargada con una temperatura incrementada en 6 a 10 ºC respecto a la temperatura ambiente (Poornima et al 2006), pudiendo alterar localmente la estructura comunitaria del plancton (Poornima et al 2006, Jiang et al 2009), bentos (Schiel et al 2004) y peces (Teixeira et al 2009). Si sumamos otros factores de calentamiento de las aguas (e.g., El Niño), la tolerancia térmica de muchas especies puede ser sobrepasada (Zargar & Ghosh 2007).…”
Section: Bajo La Sombra De Las Termoeléctricasunclassified